Effect of the Use of Metakaolin Artificial Lightweight Aggregate on the Properties of Structural Lightweight Concrete - Puput Risdanareni; Afif Achsanul Choiri; Boedya Djatmika; Poppy Puspitasari (Civil Engineering Dimension, 2017)
This paper investigates the effect of using metakaolin Artificial Lightweight Aggregates (ALWA) as a substitute for coarse aggregates to produce structural lightweight concrete. A combination of 10M NaOH solution and sodium silicate solution was used as alkali activator. The ratio between the metakaolin binder and the alkali activator used in producing metakaolin ALWA is 48%:52%, by mass. It is shown that metakaolin ALWA has higher abrasion and water absorption, and lower bulk density values compared to normal aggregates. To determine the effect of using metakaolin ALWA as coarse aggregates in concrete, three variations of ALWA dosages were used, i.e. 0%, 50%, and 100% of the total coarse aggregates, by volume. The results show that the compressive strength of concrete decreased along with the increase of ALWA content in the mixture. However, concrete using 100% ALWA as coarse aggregates meets the requirements of compressive strength and density of structural light weight concrete.